Hydrological and ichthyological survey of the small river Gorodskaya (Paramushir Island, Northern Kuriles, Sakhalin Region) - T. Y. Uglov; A. V. Sokolov; A. I. Nikiforov (Известия ТИНРО)
This paper presents the results of a comprehensive hydrologic-ichthyological route survey of the main part of the Gorodskaya River channel (Paramushir Island, Northern Kurils, Sakhalin Oblast) conducted in June 2021. The purpose of this survey was to determine the presence of native ichthyofauna components and to clarify a number of hydrologic and hydrobiological characteristics of the Gorodskaya River. As a result of the route survey, no ichthyofauna components were found in the waters of the Gorodskaya River; a number of bathymetric and hydrologic characteristics of the surveyed watercourse were updated in the course of the work.